China's economic revolution - Eckstein, Alexander (Cambridge : New York : Cambridge University Press, 1977)
Professor Eckstein's book is a study of China's efforts to achieve rapid modernization of its economy within a socialist framework. Eckstein begins with an examination of economic development in pre-Communist China, specifically focusing on the resources and liabilities inherited by the new regime in 1949 and their effects on development policies.
Includes bibliographical references and index.
asm 22/01/2019
Loans
Keywords: Economic conditions; Economic history; Economic policy; Economics; China